HAMI 3379, a CysLT2R antagonist, dose- and time-dependently attenuates brain injury and inhibits microglial inflammation after focal cerebral ischemia in rats. (16th April 2015) - Shi, Q.J.; Wang, H.; Liu, Z.X.; Fang, S.H.; Song, X.M.; Lu, Y.B.; Zhang, W.P.; Sa, X.Y.; Ying, H.Z.; Wei, E.Q.
Highlights: We determined the neuroprotective effect of the CysLT2 R antagonist HAMI 3379. HAMI 3379 dose- and time-dependently protects rats from ischemic stroke. The effective dose is 0.1 ∼ 0.4 mg/kg and the therapeutic window is 1 h. HAMI 3379 has the effects on ischemic brain injury similar to pranlukast. It selectively attenuates microglia-related post-ischemic inflammation. Abstract: Cysteinyl leukotrienes (CysLTs) induce inflammatory responses by activating their receptors, CysLT1 R and CysLT2 R. We have reported that CysLT2 R is involved in neuronal injury, astrocytosis, and microgliosis, and that intracerebroventricular (i.c.v.) injection of the selective CysLT2 R antagonist HAMI 3379 protects against acute brain injury after focal cerebral ischemia in rats. In the present study, we clarified features of the protective effect of intraperitoneally-injected HAMI 3379 in rats. We found that HAMI 3379 attenuated the acute brain injury 24 h after middle cerebral artery occlusion (MCAO) with effective doses of 0.1–0.4 mg/kg and a therapeutic window of ∼1 h. It attenuated the neurological deficits, and reduced infarct volume, brain edema, and neuronal loss and degeneration 24 and 72 h after MCAO. RNA interference with i.c.v. injection of CysLT2 R short hairpin RNA (shRNA) attenuated the acute injury as well. Also, HAMI 3379 inhibited release of the cytokines IL-1β, interferon-γ (IFN-γ), and tumor necrosis factor-α (TNF-α) into the serum and cerebrospinal fluid 24 h after MCAO. Moreover, HAMI 3379 ameliorated the microglial activation and neutrophil accumulation in the ischemic regions, but did not affect astrocyte proliferation 72 h after MCAO. In comparison, the CysLT1 R antagonist pranlukast did not affect microglial activation and IFN-γ release, but inhibited astrocyte proliferation and reduced serum IL-4. Thus, we conclude that HAMI 3379 has a protective effect on acute and subacute ischemic brain injury, and attenuates microglia-related inflammation. CysLT2 R antagonist(s) alone or in combination with CysLT1 R antagonists may be a novel class of therapeutic agents in the treatment of ischemic stroke.